PENGARUH SUDUT BEBAS PAHAT TERHADAP KEKASARAN PERMUKAAN BAHAN ST.37 PADA PROSES PERMESINAN SEKRAP - Sriyanto Sriyanto; Edy Iryanto; Suhartoyo (KOLONI, 2022)
Metalworking for production process activities is one of the uses of metal materials for production, namely ST.37 objects because for this material the processing process is very easy and widely used. Metal working is done using a scrap machine, for the process it requires machining settings and tool geometry. Precise parameter setting, surface roughness quality as expected. The research parameters are the cutting speed and the angle of inclination of the tool. In this study, the variation of the tool angle and the cutting speed used was varied so as to produce the best variation, namely the smallest roughness value. Variations in the free angle of the cutter blade were made with variations of 5°, 10°, and 15°. Variations in machining settings were cutting speed 16 m /min,20.8m/min and 25.6m/min. With a fixed feeding depth of 0.3mm. In the initial step, the cutting chisel is sharpened with different free angle geometries, then the chisel is installed on the tool holder, put the workpiece on the vise, set the cutting speed, feeding depth, and perform the machining process. °,10° and 15° with cutting speeds of 16 m/min, 20.8 m/min and 25.6 m/min, respectively, with 3 experiments. Subsequent experimental results were averaged. For the best results with an average roughness of 4.34 m obtained from a tool angle of 15° with a cutting speed variation of 16 m/min..   Keywords: Scraping machine, chisel geometry, cutting speed, surface roughness, surface roughness tester.